Profile of Non-communicable Disease Risk Factors Among Young People in Palau - Chiang, Chifa (J Epidemiol, 2015)
BACKGROUND: Although non-communicable diseases (NCDs) have become the predominant health problems of Palauan society, there have been no comprehensive data on NCD risk factors available to develop effective control strategies. Therefore, the first Palauan national STEPwise approach to risk factor Surveillance (STEPS) was completed in mid-2013 to provide information on its adult population aged 25 to 64 years. This study aims to obtain corresponding data from the younger adults aged 18 to 24 years, who remained to be surveyed. METHODS: We conducted an epidemiological study, targeting the 18- to 24-year-old age group. A survey station and a mobile team were established to recruit voluntary participants dwelling in Koror. A slightly modified WHO STEPS instrument was used, including a structured questionnaire for behavioral risk factors, physical measurements, and blood tests. RESULTS: A total of 356 young people were recruited during the survey. In both sexes, nearly half of the participants were overweight/obese. The prevalence of hypertension was higher in men than in women (17.6% vs 1.7%). Raised blood glucose and impaired fasting glucose were observed in 3.5% and 5.2% of the total participants, respectively. About 36% of the subjects were observed to have raised levels of total cholesterol. More than 70% of the young people were current tobacco users, in terms of all kinds of tobacco products. CONCLUSIONS: The current survey, for the first time, revealed a high prevalence of NCD risk factors, especially overweight/obesity and tobacco use, among young people in Palau. This indicates that swift measures against NCDs are required even in this young age group.